Direct Visualization of Atomic Structure in Multivariate Metal‐Organic Frameworks (MOFs) for Guiding Electrocatalysts Design. (14th December 2022) - Sun, Dengrong; Wong, Lok Wing; Wong, Hok Yin; Lai, Ka Hei; Ye, Lin; Xv, Xinyao; Ly, Thuc Hue; Deng, Qingming; Zhao, Jiong
Abstract: The direct utilization of metal–organic frameworks (MOFs) for electrocatalytic oxygen evolution reaction (OER) has attracted increasing interests. Herein, we employ the low‐dose integrated differential phase contrast‐scanning transmission electron microscopy (iDPC‐STEM) technique to visualize the atomic structure of multivariate MOFs (MTV‐MOFs) for guiding the structural design of bulk MOFs for efficient OER. The iDPC‐STEM images revealed that incorporating Fe 3+ or 2‐aminoterephthalate (ATA) into Ni‐BDC (BDC: benzenedicarboxylate) can introduce inhomogeneous lattice strain that weaken the coordination bonds, which can be selectively cleaved via a mild heat treatment to simultaneously generate coordinatively unsaturated metal sites, conductive Ni@C and hierarchical porous structure. Thus, excellent OER activity with current densities of 10 and 100 mA cm −2 are achieved over the defective MOFs at small overpotentials of 286 mV and 365 mV, respectively, which is superior to the commercial RuO2 catalyst and most of the bulk MOFs. Abstract : The low‐dose integrated differential phase contrast‐scanning transmission electron microscopy (iDPC‐STEM) technique is utilized to visualize the structure and resolve the lattice strain information of multivariate MOFs (MTV‐MOFs) at an atomic level, providing important guidance in the further design of MOFs for efficient OER.